Contamination and health risk assessment of heavy metals in soil surrounding an automobile industry factory in Jiaxing, China - Liu, Tingting; Ni, Sheng Yue; Wang, Zhen (Frontiers in Environmental Science, 2024)
The auto parts industry occupies an important strategic position in our national economy, which brings about the pollution problem in the processing of auto parts, particularly in soil polluted by heavy metals. Soil samples were collected from an automobile parts company in Jiaxing, China, and the data were evaluated using the land accumulation index method. The study found that the heavy metal pollution in the downwind direction of the Automobile Parts Co., Ltd. is mainly As, CD, and Zn mixed heavy metal pollution, and the distribution is uneven. The coefficient of variation of As was the largest, and the regional variation amplitude was large. The coefficient of variation of CD, Cr, and Ni is 50%, that of Zn is 39.38%, and that of PB is the lowest. The accumulative index of AS and CD was 6, which was a very serious pollution level.The content of As was 1994.7 mg/kg, exceeding the standard by more than 44 times, and the distribution of As in soil was uneven. The pollution level of Zn is 3, which belongs to the moderate level. The pollution degree of heavy metals in the soil decreases as the distance from the downwind outlet of the plant increases. According to the health risk assessment, the main route of heavy metals entering the body is through the mouth by breathing. Among exposure routes, oral exposure to heavy metals is the most harmful, so we need to pay special attention to farmland soil heavy metal pollution.